(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Importance of the work consists in studying the influence of quercetin and some metabolic preparations in treatment of experimental diabetes. Purpose. Possibility of correction of the disturbances of the enzymic processes in mitochondria of the retina in experimental diabetes. Methods. The investigations were made on Wistar white rats with 190—210 g in mass. Three groups of animals with developing diabetes received lipoic acid, perorally, quercetin and methionine (S-adenosylmethionine). Activity of the enzymatic systems of mitochondria of the retina was determined by means of methods of spectrophotometric analysis. Results. The degree of disturbances of the oxidation-reduction and transport processes in retinal mitochondria in experimental diabetes was noticeably lowered under the influence of preparations of the lipoic acids, quercetin and methionine. Conclusions. Application of quercetin exerted distinct influence on the condition of the oxidation-reduction and transmembraneous processes in the retinal mitochondria in experimental diabetes. Metabolic preparations (lipoic acid and S-adenosylmethionine) evidently limit disturbances of activity of the enzymatic system of the retinal mitochondria in streptozotocynic diabetes.